(untitled) (International Journal of Environmental Sciences, 2025)
Among the European communities that migrated voluntarily or by force, German groups migrated to Latin America and spread across its various islands and territories, especially during the period of European colonialism after 1500. Tracing historical stages, we find that Germans had a presence during that period. Historical studies specializing in the activity of liberation movements in the diaspora are a component of historical and political studies. There, Latin American countries were among the most important continents that attracted numerous global migrations, especially those coming from Europe since the beginning of the twentieth century. It was a land where various human races met to start a new life in an attempt to sever ties with the past. However, political changes in Europe, including the activity of some nationalist movements, led to the outbreak of World War I, which swept through most regions of the world, including Latin America. These human elements of European origin, including Germans, were the focus of attraction for thousands of their ethnic and compatriots to immigrate after World War I in 1918. The subject of our research was chosen to trace the German presence in Latin American countries, namely Argentina.